Peranan Terapi Spiritual Terhadap Penyembuhan Adiksi Narkoba (Studi di Inabah XX Tasikmalaya Jawa Barat) - Didin Komaruddin; Ilim Abdul Halim (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2021)
Along with the rapid development of the globalization era, many influences on human life, various contexts of problems occur, especially narcotics problems, until this moment it is still a very serious phenomenon. Therefore, various ways globally continue to be carried out both with national, regional and international cooperation in order to eradicate this narcotics abuse. In addition, an approach that has tended to emphasize more on the security approach has now changed to a balanced approach between security, health and religion. For this reason, Inabah XX deals with healing narcotics addiction using Islamic therapy and one of them is spiritual therapy. In carrying out Inabah XX, it treats the repentance, prayer, dhikr, and fasting bathing methods. The purpose of this paper is to find out how this spiritual therapy method is applied to healing narcotic addiction in Inabah XX and how this spiritual therapy process is towards healing narcotics addiction in Inabah XX healing center. Spiritual therapy itself is the appreciation and condition of a servant who is close to his god through the teachings of the context of worship to improve the quality of action and life through a process of marking with the body and brain as the area of activity. From the results of the writing shows that spiritual therapy in Inabah XX can cure and revive narcotics addiction. With several methods such as bathing at night or bathing repentance, midnight prayer, dhikr and fasting This is proven by the process of healing from the night bath at 02.00 followed by the midnight prayer, remembrance to worship and other practices as a daily routine experienced by narcotics addicts so this makes narcotics addicts who were addicted to drugs become free of life and feel more free calm when facing problems.